Contemporary Management of Zygomaticomaxillary Complex Fractures - Wang, Howard D.; Dillon, Jasjit (Seminars in Plastic Surgery, 2021)
Zygomaticomaxillary complex fracture is one of the most commonly treated facial fractures. Accurate reduction and stable fixation of the zygoma are required to restore facial symmetry and projection and avoid functional sequalae from changes in orbital volume. Achieving optimal outcome is challenging due to the complex three-dimensional anatomy and limited visualization of all affected articulations of the zygoma. This article provides an updated overview of the evaluation and management of zygomaticomaxillary complex fractures based on available evidence and clinical experience at our center. The importance of soft tissue management is emphasized, and approaches to internal orbital reconstruction are discussed. While evidence remain limited, intraoperative imaging and navigation may prove to be useful adjuncts in the treatment of zygomaticomaxillary fractures.
Keywords: zygoma fracture; zygomaticomaxillary complex; orbital fractures; facial fracture; open reduction and internal fixation